New records of Diptera from Lagodekhi Reserve, Sakartvelo (Georgia), with descriptions of new species - Brice, David; Lonsdale, Owen; Macgowan, Iain; Oboňa, Jozef; Weele, Ruud Van Der; Zuijlen, Jan Willem Van; Whitmore, Daniel; Japoshvili, George (Zootaxa, 2026)
Sixteen families were studied from the survey presented here, seven of which were new to Georgia. Of the 62 genera identified, 54 represent new country records. Of the 140 recorded species, 111 are new records for Georgia, whereas 10 are new for science and described here for the first time. The most diverse family was Sphaeroceridae with 39 species, followed by Agromyzidae with 27. Of the newly described species, seven belong to Agromyzidae: Liriomyza priapus Lonsdale, sp. nov.; Phytomyza (Napomyza) alata Lonsdale, sp. nov.; Phytomyza (P.) affinoides Lonsdale, sp. nov.; Phytomyza (P.) orphne Lonsdale, sp. nov.; Phytomyza (P.) pilosinomia Lonsdale, sp. nov.; Phytomyza (P.) skia Lonsdale, sp. nov.; Phytomyza (P.) villosus Lonsdale, sp. nov.; and three to Sphaeroceridae: Copromyza pileus Brice, sp. nov.; Gonioneura lagodekhiensis Brice, sp. nov.; and Terrilimosina irwini Brice, sp. nov.